THIOPHENE CRACKING USING MAGNESIUM MODIFIED BETA ZEOLITE - Santos, Ronaldo Costa (2018)
The development of additives for FCC catalysts aiming at a greater sulfur removal in the gasoline fraction has been a priority with tougher environmental legislation demands. In this context, this study has evaluated the effect of magnesium modified beta zeolite on n-hexane cracking, and the catalytic conversion of thiophene added as contaminant. Catalytic tests’ results, performed at low conversion at 400 ºC with a WHSV of 0.83 s-1 indicate that magnesium addition increased n-hexane cracking from 37.7 to 53.6% in mols, but favored the formation of alkylated sulfur compounds over H2S production.